2017
DOI: 10.1007/s10803-017-3145-x
|View full text |Cite
|
Sign up to set email alerts
|

Autism in Southeast Europe: A Survey of Caregivers of Children with Autism Spectrum Disorders

Abstract: The aim of this study was to understand the diagnostic, service and lived experiences of families affected by ASD in Southeast Europe. A total of 758 caregivers from Albania, Bulgaria, Croatia and Turkey were surveyed from 2013 to 2015 about characteristics of the child with ASD; service encounters; and caregiver perceptions. The average age at first concern was 24.4 months (SD 11.8) and at diagnosis, 40.0 months (SD 19.0). Psychiatrists were the most common diagnostician; most children received some ASD-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 25 publications
7
44
0
7
Order By: Relevance
“…Most of the available studies have been conducted in the United States, Canada, and other Englishspeaking countries. Although we found a small number of studies, concerning mostly children, conducted in Western Europe [20] and Southeastern Europe [21], to our knowledge, there is no study published in an international journal on services for adolescents and adults with ASD in Central and Eastern Europe. Therefore, little is known from previous studies about the patterns of service use and needs that can be generalized to other countries across various sociocultural, economic, and systemic factors.…”
Section: Introductionmentioning
confidence: 83%
“…Most of the available studies have been conducted in the United States, Canada, and other Englishspeaking countries. Although we found a small number of studies, concerning mostly children, conducted in Western Europe [20] and Southeastern Europe [21], to our knowledge, there is no study published in an international journal on services for adolescents and adults with ASD in Central and Eastern Europe. Therefore, little is known from previous studies about the patterns of service use and needs that can be generalized to other countries across various sociocultural, economic, and systemic factors.…”
Section: Introductionmentioning
confidence: 83%
“…Affiliate stigma could lead the parents to react behaviorally by hiding their children's condition from others, withdrawing from social relations, or alienating themselves from the stigmatized individuals to avoid association [28,29]. There are a few studies that have reported a high level of affiliate stigma in the parents of children with ASD [27,[30][31][32][33]. Affiliate stigma is also found to negatively affect psychological well-being in these parents, leading to a reduced quality of life [24,27,30].…”
Section: Introductionmentioning
confidence: 99%
“…Croatian respondents, like families elsewhere (Daniels et al ., 2017), spoke of their experience of discriminatory behaviour and stigmatisation. In many cases, this was enacted through social exclusion, leading one parent to state that other people needed to understand that
‘autism is not a contagious disease, that that is not a reason you should separate your children from our children .
…”
Section: Some Key Findings and Commentarymentioning
confidence: 99%
“…However, PE in autism is not accessible by all and is limited or unavailable in many regions, including south‐east Europe (Daniels et al ., 2017; Hansen et al ., 2017). A three‐year European Commission‐funded project, Equity and Social Inclusion through Positive Parenting (ESIPP), was established in 2015 to address this shortfall for families in Croatia, Cyprus and North Macedonia.…”
Section: Introduction: Parent Education In Autism and The Esipp Projectmentioning
confidence: 99%